INFLUENCE OF POVERTY ON FEMALE YOUTH PROSTITUTION IN UGANDA: THE EXPERIENCES OF YOUNG WOMEN RESIDING IN KIGONGI WARD, KABALE MUNICIPALITY. - Ruth Mbabazi; Adebayo Sanni Tajudeen (Student's Journal of Health Research, 2023)
Background: The study aimed to investigate the influence of poverty on female youth prostitution in Kigongi Ward, Kabale Municipality. The study was guided by specific objectives, which include the influence of poverty on female youth prostitution, the experiences and perspectives of the female youth involved in prostitution, and the degree to which poverty influences prostitution among female youths in Kigongi Ward, Kabale Municipality. Methodology:  This study adopted a case study research design utilizing both quantitative and qualitative approaches. Using simple random and purposive sampling techniques, a total of 100 respondents were used in the study. Results:  It was found that a majority of 30% of the respondents reported that a woman might live a simple life or earn a lot of money as a prostitute, while 20% of the respondents mentioned parental neglect and youth laziness as the factors that push female youth into prostitution. Also, (30%) of respondents mentioned that prostitution affects a community's reputation, standard of living, and property. On the degree to which poverty influences prostitution among female youths, the majority of the respondents (45%) said that poverty causes female youth prostitution in Kigongi Ward. Conclusion:  It was concluded that poverty contributes majorly to female youth prostitution in the Kigongi ward of Kabale Municipality. And there is no supportive empowerment policy that can alleviate poverty. Recommendation:  People from developing nations must be given legal chances to migrate, with consideration for the economic interests of both the receiving nation and the immigrants themselves.